Pengaruh Penerapan Kurikulum Merdeka dengan Karakter Siswa di Sekolah Dasar - Tessa Lonika Simanullang; Nadia Melisa Damanik; Grecia Gustri Malona Sitinjak; Siti Syahira; Muhammad Ikhlas (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
The independent curriculum is an innovation in Indonesian education that offers freedom to learn to students, and allows educational units, teachers, and students to design learning processes that are relevant to their individual needs and potential, with an emphasis on developing student character. This study aims to describe in detail how the role of the Independent Curriculum in the formation of student character. This study was compiled with a literature study or Library observation. Data in this literature study were collected through searches on Google Scholar and various other databases, which aim to obtain comparative material. After that, the data that was successfully collected was collected based on its relevance to the research questions and objectives of this article, then summarized into comprehensive study results. The data collection process was carried out by tracing literature from national and international journals available on several websites. The results of the study show that the Independent Curriculum in Indonesia is designed to be freedom for students in the learning process through a flexible approach that is relevant to their lives. This curriculum forms student character based on Pancasila values, using various strategies such as differentiated learning, project-based learning